Rice Protein as a Functional Carrier: Recent Updates on Modification Strategies and Encapsulation Applications - Sun, Yaping; zhao, zhengtao (Food and Feed Research, 2026)
Rice protein (RP), owing to its favorable nutritional profile, biodegradability, and biocompatibility, has emerged as a promising plant-based carrier for bioactive compound delivery. However, its poor water solubility, low emulsifying capacity, and rigid molecular structure limit its application in functional food systems. Recent advances have focused on physical, chemical, and enzymatic modification strategies to enhance RP’s solubility and other functional properties. These improvements facilitate its incorporation into various encapsulation formats such as emul-sions/nanoemulsions, micro/nanoparticles, edible films, and hydrogels. This review summarizes current progress in RP modification and its impact on encapsulation performance, including stability, bioactive protection, and controlled release. It also explores the interaction mechanisms between RP and bioactives and highlights challenges such as limited mechanistic insight. Future research should aim to develop food-grade, mild modification methods and investigate the digestive fate and bioavailability of RP-based delivery systems for functional food and nutraceutical applications.